Mexican beliefs and attitudes toward menopause and menopausal-related symptoms. (March 2013) - Marvan, Maria Luisa; Castillo-López, Rosa Lilia; Arroyo, Laura
Abstract: The objective of this study was to explore the beliefs and attitudes toward menopause among young and middle-aged Mexican women and men, as well as the menopausal-related symptoms that middle-aged women report or expect and that other participants think a menopausal woman experiences. The beliefs about and attitudes toward Menopause Questionnaire and the Greene Climacteric Scale were answered by 395 Mexicans between the ages of 20 and 60 years. Comparing middle-aged participants, the most negative attitudes toward menopause were held by surgically menopausal women, and the most positive attitudes by naturally postmenopausal women. Younger participants showed more negative attitudes when compared to those in middle age (with exception of surgically menopausal women). There was a positive correlation between negative attitudes and menopausal-related symptoms either experienced by perimenopausal and naturally postmenopausal women, or expected by young and premenopausal women. No significant correlation was found between attitudes and symptoms in the groups of surgically menopausal women or the men. These findings are discussed in light of differences between genders and age cohorts.